A study on prevalence and factors contributing to self medication practice among health science students of Nepal institute of health sciences, Jorpati -1, Kathmandu, Nepal. - Pokharel, Sushma (2014)
ABSTRACT: This study was a quantitative, cross-sectional study conducted to assess the prevalence and to identify the factors contributing to self medication practice among the health science students of Nepal Institute of Health Sciences (NIHS) Jorpati-1. A sample of 236 students was selected through stratified random sampling from total 511 students. The participants were provided with the semi-structured questionnaire to fill up by themselves (self administered). The study variables were categorized as dependent and independent variables. The dependent variable was self medication practice and the independent variables were age, sex, educational level, specific field of study, study year, religion, health status, previous experience about similar drugs and illness, source of information, knowledge about drugs and side-effects, lack of time to visit health care facility and nature of disease. The statistical software SPSS window-16 was used to entry and analyzed the data. The statistical analysis like frequency and percentage table was performed for univariate analysis. Bivariate analysis was done using chi-square statistics. The major findings of the study revealed that the prevalence of self medication among health science students was found to be 66.9%. The major reason for self medication practice was found to be disease not serious (37.3% response), previous experience of drugs and similar illness (24% response), and emergency condition (20% response). The main source of information about drugs is opinion of friends/seniors (23% response), opinion of family members (15.5% response), recommendation by community pharmacy(11.3% response) . The selection of drugs was mainly based on own previous experience about drugs (28.6% response). Most of the respondents used OTC medications for fever (24.05%), headache (19.62%), common-cold (17.72%), tonsillitis (14.55%) and majority of them used NSAID including paracetamol (53.79%), anti-cold (17.72%), anti-gastritis (9.49%), and anti-biotics (8.22%). Most of the respondents had adequate knowledge about drugs they self medicate and aware about side--effects. The findings of the study also revealed that there was significant association between age educational level, specific field of study with self medication practice whereas sex, study year, religion and current health status were not found significantly associated with self medication practice. Half of the respondent found self medication as an acceptable practice. This study concluded that self medication practice is common among health science students. The prevalence is high among educated youths who are aware of the harmful impacts. Therefore, it is necessary to raise awareness and emphasis on the pros and cons of the self medication practice to ensure safe practice. Also the government should reinforce strict rules and regulation for the sales of drugs with potentially harmful effects and implement effectively.